123k views
4 votes
(x^3-2x^2+3x-4)(x-1)-(2x-3)(x^2-x+1)​

User Onik
by
5.1k points

1 Answer

2 votes

Answer:

x^4−5x^3+10x^2−12x+7

Explanation:

Distribute:

=(x^3)(x)+(x^3)(−1)+(−2x^2)(x)+(−2x^2)(−1)+(3x)(x)+(3x)(−1)+(−4)(x)+(−4)(−1)+−2x^3+5x^2+−5x+3

=x^4+−x^3+−2x^3+2x^2+3x^2+−3x+−4x+4+−2x^3+5x^2+−5x+3

Combine Like Terms:

=x^4+−x^3+−2x^3+2x^2+3x^2+−3x+−4x+4+−2x^3+5x^2+−5x+3

=(x^4)+(−x^3+−2x^3+−2x^3)+(2x^2+3x^2+5x^2)+(−3x+−4x+−5x)+(4+3)

=x^4+−5x^3+10x^2+−12x+7

User Artoodetoo
by
4.9k points